PARACLINICAL PREDICTORS OF UNFAVORABLE OUTCOMES FOR THE FETUS DURING DELIVERY AT 41 OR MORE WEEKS IN PATIENTS WITH HIGH PERINATAL RISK - Ольга Александровна Бельницкая; Елена Станиславовна Кравцова; Оксана Николаевна Фильчакова; Татьяна Ивановна Горбачева (The Publishing House Medicine and Enlightenment, 2016)
In order to identify paraclinical risk factors for adverse outcomes for the fetus during delivery at term of 41 or more weeks of high perinatal risk patients, the STV index informativeness was evaluated in 240 pregnant women, 75 of them were determined with the content of lactate and 61 - with the matrix metalloproteinase-1 in the amniotic fluid waters and their informative value in predicting the outcome of childbirth was assessed. Studied markers allow assessing the risk of suffering hypoxia in fetal first stage of labor (amniotic fluid lactate + STV), and predict pathological outcome of birth (matrix metalloproteinase-1 in the amniotic fluid) in the form of cerebral ischemia in neonatal early neonatal period.